2016
DOI: 10.21475/ajcs.2016.10.04.p7364x
|View full text |Cite
|
Sign up to set email alerts
|

Growth, nutrition and production of dry matter of Kikuyu Grass (Brachiaria humidicula) as a function of Mn-fertilizer

Abstract: Manganese (Mn) is important to increase forage crop yields. However, there is little information regarding the adequate Mn-fertilizer rates for Brachiaria humidicula species. The objective of this research was to evaluate the effect of manganese on growth, nutrition and yield of Brachiaria humidicula. The study was carried out in a green house in a randomized block design with five rates of manganese (0, 15, 30, 60 and 120 mg dm -3 ) and four replicates. Were evaluated plant height, leaf area, relative chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…These results are similar to those observed by Arruda et al, (2016), who showed higher concentrations of Mn 2+ in Urochloa humidicula at the second cut. They attributed this increase in Mn 2+ concentration to the greater root development compared with the first cut, which favored the nutrient absorption (Arruda et al, 2016). Guirra et al (2011) and Sylvestre et al (2012) observed the same pattern when assessing the effect of Mn in Tanzania grass (Panicum maximum) and Urochloa brizantha cv.…”
Section: + Content In Roots and Shootsupporting
confidence: 92%
See 4 more Smart Citations
“…These results are similar to those observed by Arruda et al, (2016), who showed higher concentrations of Mn 2+ in Urochloa humidicula at the second cut. They attributed this increase in Mn 2+ concentration to the greater root development compared with the first cut, which favored the nutrient absorption (Arruda et al, 2016). Guirra et al (2011) and Sylvestre et al (2012) observed the same pattern when assessing the effect of Mn in Tanzania grass (Panicum maximum) and Urochloa brizantha cv.…”
Section: + Content In Roots and Shootsupporting
confidence: 92%
“…The absorption efficiency of Mn (AB ef ) did not differ among the evaluated Mn rates. In Urochloa humidicola Arruda et al, (2016) observed an enhanced AB ef with the increase of Mn doses. Since this nutrient is toxic when its level is high in soil, these results suggested that Guinea Grass may is less susceptible to the toxic stress by Mn than Urochloa humidicola.…”
Section: Efficiency Indices: Absorption Transport and Utilizationmentioning
confidence: 90%
See 3 more Smart Citations